Optimizing Digital Visibility: A Comprehensive Analysis and Implementation of Paid Google Ads - Zusnita, Wa Ode Zusnita Muizu; Angel, Angeliqa Michelle Putri; Dara, Dara Sagita Triski (Research and Social Study Institute (RESSI), 2024)
Google AdWords, commonly referred to as paid Google Ads, is a pay-per-click advertising platform that enables businesses to promote their offerings through ads seen on the Google search engine and affiliated websites. The objective of employing the paid GoogleAds strategy is to enhance the online prominence of United Tractors' products by leveraging the paid GoogleAds approach to optimize visibility. This approach starts by analyzing the existing digital landscape. This audit encompasses an assessment of the company's website, social media presence, and existing online advertising endeavors. Subsequently, the research will give priority to the development of a thorough strategy for sponsored Google Ads. This assignment entails the identification of the most optimal keywords and ad formats for United Tractor’s products. This strategy will include a complete framework of methodologies for monitoring and assessing the efficacy of advertising, enabling ongoing refinement and enhancement. Upon deploying the paid Google Ads package, we will evaluate its influence on United Tractors online presence. In the end, this approach will lead to a complete plan to enhance United Tractor's online presence by leveraging sponsored Google Ads. Enhancing online visibility enables United Tractors to enhance brand awareness, attract a larger pool of prospective clients, and eventually boost sales growth.